Mind Mapping Methods Using to Improve Student Learning Outcomes of Social Studies Learning in Class VII-F 7 Bandung Junior High School (Classroom Action Research at Class VII-F 7 Bandung Junior High School) - Faisal, Budi Nur (Universitas Pendidikan Indonesia, 2017)
Abstract-This research is motivated by the problems that researchers find in the learning process of social studies related to the low student learning outcomes. The issues raised in this study about improving student learning outcomes through the use of mind mapping method in social studies learning. Learning outcomes are characterized by changes in behavior. While Mind Mapping is a way of recording a creative and effective, easy way to enter and release information in the brain that suits the workings of the brain. So mind mapping can be an alternative method to improve student learning outcomes. This study aims to describe how planning, implementation, results, and efforts to overcome obstacles in an effort to improve student learning outcomes through mind mapping method in social studies learning in class VII-F 7 Bandung Junior High School. The research method used is classroom action research with Kemmis Taggart design. The source of this research data is the improvement of learning outcomes through the use of mind mapping method in social studies learning. Indicator of learning outcomes in this study is to remember, understand, apply, create, and Attitudes. In the indicators of understand and remember there is an increase in each cycle. In addition to the improvement of the post test results in each cycle. The general conclusion is the use of mind mapping method can improve students' learning outcomes in social studies learning at class VII-FKeywords: Learning Outcomes in Social Studies, Mind Mapping.